Efeito do caroço de algodão na modulação de fibras musculares esqueléticas e qualidade de produtos de carne ovina - Monego, Magda Aita (2018)
The aim of this study was to evaluate the modulation of skeletal muscle fibres from Ile de France lambs fed with levels of whole cottonseed (WCS), as well as to develop sheep meat products and characterise them. This study was composed of three experimental tests. The first evaluated the serum levels, modulation, and performance of skeletal muscle fibres of Longissimus thoracis of Ile de France lambs fed with whole cottonseed and its relation to meat quality. The skeletal muscle fibres were identified by histochemical analysis and classified according to contraction velocity, staining and metabolism. Fifty Ile de France lambs, five references and five treatments (0, 10, 20, 30 and 40% WCS in the diet) were used, with nine replicates and a completely randomised design. The linear and quadratic trends, as well as the Spearman partial correlation between fibre characteristics and meat quality (58 variables) were evaluated, with whole cottonseed levels being used as covariates. Serum cholesterol, total protein and gamma glutamyl transpeptidase levels increased (P<0.05) according to the level of inclusion of whole cottonseed. The effect of time (reference × WCS) on the modulation of muscle fibres, with an increase (P<0.05) of red fibres, reduction (P<0.05) of glycolytic fibres, and transition (P<0.05) of Type IIB to Type IIA fibres was observed. The effect of the diet was observed only for the variable relative area of Type IIC fibres, with a linear tendency that increased according to the inclusion of whole cottonseed. It was concluded that the effect of time (reference × CA) was more pronounced than the effect of diet on the characteristics of muscle fibres, which was correlated with meat quality. In the second and third experiments, the physicochemical, technological and sensorial properties of hamburger and meatballs that were prepared with meat from lambs fed on different levels of whole cottonseed were evaluated. Each experiment was conducted in a completely randomised design, with five treatments (0; 10; 20; 30; 40% WCS) and four replicates. The data were submitted to analysis of variance (ANOVA) at 5% significance and the significant results were submitted to regression analysis. In the hamburger, the addition of whole cottonseed to the lambs' diets decreased (P<0.05) the thiobarbituric acid reactive substances in the lamb meat and altered (P<0.05) the physicochemical characteristics of the hamburgers, which were characterised by low lipid (̂= 4.27), cholesterol (̂= 75.15) and caloric content (̂= 122.04). The results regarding cooking characteristics were directly related to the microscopic observations regarding the hamburgers; the more cohesive structures exhibited better (P<0.05) performance after cooking, with increased (P<0.05) cooking yield and moisture retention and decreased (P<0.05) cooking loss. The levels of whole cottonseed did not influence (P>0.05) the texture profile, but they negatively affected the acceptability of the hamburgers (P<0.05); as the levels of whole cottonseed increased the scores for the sensorial attributes decreased (P<0.05). Thus, for hamburger formulations, a maximum inclusion of 16.7% WCS in the dry matter of the diet of lambs is recommended. The meatballs prepared with lamb from animals fed on whole cottonseed presented higher (P<0.05) ash content. All the meatball formulations presented low levels of lipids (̂= 2.90) and cholesterol (̂= 74.15 mg/100g), as well as high protein content (̂= 18.92). The difference (P<0.05) observed in the variables of the cooking characteristics did not influence the texture profile, which was related to the microscopic observations of the product. In the triangle test for difference, the testers did not perceive difference between the control meatballs (0% WCS) and those with up to 30% WCS. However, in the acceptance test the testers detected sensory alteration starting at a level of 12.5% WCS. Thus, it is possible to produce meatballs with meat from lambs fed on up to 12.5% WCS in the dry matter of their diet without altering the sensory characteristics of the product.